2010
DOI: 10.1269/jrr.10052
|View full text |Cite
|
Sign up to set email alerts
|

G0 and G2 Chromosomal Assays in the Evaluation of Radiosensitivity in a Cohort of Italian Breast Cancer Patients

Abstract: Breast cancer (BC) is the most common type of malignancy in female patients and radio-treatment is the conventional therapy even if a great number of studies reported that enhanced sensitivity to ionizing radiation as measured as chromosome effects is present in a significant proportion of cancer patients, including breast cancer ones. In this study we analysed whether peripheral blood lymphocytes from sporadic BC patients and healthy subjects showed a different sensitivity to ionizing radiation and whether cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In our study, 89% of the patients were radiosensitive or highly radiosensitive, 11% of the patients had normal IRS and no patient was radioresistant (Table 1). The proportion of increased radiosensitive patients (89%) in this study is larger compared with numbers reported by other authors [20][21][22].…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, 89% of the patients were radiosensitive or highly radiosensitive, 11% of the patients had normal IRS and no patient was radioresistant (Table 1). The proportion of increased radiosensitive patients (89%) in this study is larger compared with numbers reported by other authors [20][21][22].…”
Section: Discussioncontrasting
confidence: 69%
“…Increased G 2 chromosomal radiosensitivity of peripheral blood lymphocytes has been associated with a number of common sporadic cancers including breast (1)(2)(3)(4)(5)(6)(7)(8)(9), colorectal (5), prostrate (10), head and neck (11,12) and a range of early-onset cancers (13) and heritability of the radiosensitive phenotype has been demonstrated (4,(14)(15)(16)(17). These observations suggest that G 2 chromosomal radiosensitivity may be a marker of inherited low penetrance cancer predisposition genes (3,5,8,18,19).…”
Section: Introductionmentioning
confidence: 91%
“…In all reported results, G2 assay able to detect the RS differences in healthy donor and breast cancer patients [135,[147][148][149][150][151][152] (Table 2). About BRCA1/2 carriers, Ernestos et al [153] and Baeyens et al [139] have reported that breast cancer patients with BRCA1 or BRCA2 mutations were not radiosensitive than healthy women carrying no mutation.…”
Section: G2/0 Chromosomal Assaymentioning
confidence: 99%
“…BC cases (515) Lymphocyte 1.5 Gy non-Hispanic White 2. Healthy controls (402) γ-rays BC cases > Healthy control Mexican American BC cases > Healthy control African Americans BC cases ↔ Healthy controls Poggioli et al 2010 [ 150 ] G0 & G2 chromosomal assay 1. BC cases (23) Lymphocyte G2 assay G0 assay & G2 assay 2.…”
Section: Radiosensitivity Assays In Breast Cancermentioning
confidence: 99%